Effect of capture frequency on the survival of Piping Plover chicks. Issue 3 (23rd August 2013) - Hunt, Kelsi L.; Catlin, Daniel H.; Felio, Joy H.; Fraser, James D.
ABSTRACT: Evaluating the possible effects of intensive research on species being studied and on the results of studies is important for both ethical and scientific reasons. We captured, banded, recaptured, and measured prefledged Piping Plover ( Charadrius melodus ) chicks during the 2010 breeding season at Lewis and Clark Lake on the Missouri River in South Dakota. We evaluated the potential for increased mortality related to frequent handling of chicks with an experiment that compared the survival of chicks handled a single time for banding ( N = 48) to chicks handled repeatedly from hatch to fledge ( N = 50). Estimates of daily survival rate (ϕ) for chicks in the two treatments did not differ (ϕsingle‐capture = 0.984 ± 0.006, ϕmultiple‐capture = 0.985 ± 0.006). Similar to previous studies, we found little evidence of increased prefledge mortality associated with frequent handling of Piping Plover chicks. However, because the effects of frequent handling of shorebird chicks may vary among species and other factors such as habitat quality (e.g., food availability), we suggest that, where possible, researchers include experiments similar to ours to evaluate possible research impacts, especially when studying threatened and endangered species.